Penguatan Reputasi Masakan Padang: Simbol Promosi Pariwisata Gastronomi dalam Film Tabula Rasa - Lukitasari, Rimalinda (Jurnal Master Pariwisata (JUMPA); Volume 06, Nomor 01, Juli 2019, 2019)
Tourism promotion through film is different from advertising due to its disguised promotion process. The application of film-induced tourism practice for tourism promotion has been widely known in the international world, but still less known in Indonesia. Utilizing film to promote tourism is not merely attaching the tourism potential into film, but is also expected to be able to help to form a positive image through the coherence of narrative and cinematic aspect of the respective film. This analysis aimed to enrich the references in the utilizing of film as one of the Indonesian tourism promotional media by identifying and interpreting the meaning of signs in the film Tabula Rasa in relation with the brand reputation strengthening of Padang culinary as part of Indonesian gastronomic tourism promotion. The analysis was done interpretive-qualitatively by using the semiotic theory as a base to interpret the signs and tourism promotion theory as the perspective of the interpretation. The result shows that the film Tabula Rasa is strengthening the brand reputation of Padang culinary by displaying brand identity, brand integrity, and image strengthening through the appearance of emotional appeals which are well packed in narrative and cinematic aspects, so that the film-induced tourism concept as a disguisedly persuasive promotional media is also fulfilled. Keywords: Tourism Promotion, Film-induced Tourism, Gastronomy Tourism, Tabula Rasa